Analisis Perkuatan Lereng Menggunakan Finite Element Method - Ongko, Andarsin; Nugroho, Soewignjo Agus; Yusa, Muhamad (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Landslides are ones of disasters which oftenly occurred in Indonesia. This research aims to analyze some slope reinforcements which are modeled by using a based finite element method software, i.e. plaxis v.8.2. As initial data, slope`s dimension was measured from real field, and soil samples were taken to obtain the soil properties. Those data were used as input parameters in modeling. The slope was modeled in several conditions, i.e. existing condition, variation of ground water table, reinforcement with backfill model, terraces model, and soil nailing model. The results shown that safety factor has decreased due to the increment of ground water table. The highest safety factor was reached when the slope was reinforced with soil noiling model, with the magnitude of 2,044.Keywords : landslides, finite element method, soil nailing, safety factor.